What is the Image of Microscale Chemistry Research for Chemistry Teaching in 2013-2023? - Hidayah, Fitria Fatichatul; Indriyanti, Dyah Rini; Madnasri, Sutikno (Jurnal Inovasi Pendidikan IPA, 2024)
This research aims to reveal the distribution of microscale chemistry research related to publication output, document sources, microscale chemistry publishing countries; countries of correspondent authors on microscale chemistry; number of annual distribution of publication affiliations of microscale chemistry; distribution of microscale chemistry publication sources; the most relevant author in microscale chemistry publications; visualization of microscale chemistry research topics and trends. The method used is a bibliometric study sourced from the scopus.com database. Data were collected through searching publications with the keyword "microscale and chemistry" in the title, abstract, or keywords determined by the author, limited to the last 10 years (2013-2023), and managed and analyzed using Software R with Biblioshiny. The results show that there is a 10-year limitation, 196 publications were obtained. The top country to publish it is the USA. The country with the most correspondent authors of a single type is the USA. The distribution analysis result shows the research topic produces data on 1000 items with 19 clusters, with the most frequently used keywords being "microscale lab", "chemistry", and "green chemistry". The existence of microscale chemistry can make chemistry practicum activities easier, providing an alternative to chemistry practicum for those who are hampered by laboratory problems.